Computerized Dual-Task Testing of Gait and Visuospatial Cognitive Functions; Test-Retest Reliability and Validity - Szturm, Tony J.; Sakhalkar, Vedant S.; Kanitkar, Anuprita; Nankar, Mayur (Frontiers in Human Neuroscience, 2017)
Abstract The common occurrence of age decline in mobility and cognition does cause a decrease in the level of physical activity and an increased falls risk. Consequently, dual -task (DT) assessments that simultaneously address both mobility skills and cognitive function are important because continued difficulties and fall injuries will have a sizable impact in this population. The first objective of the present study was to establish test-retest reliability of a computerized DT treadmill walking protocol and concurrent outcome measures of gait and visuospatial executive function in a group of healthy older adults. Secondly, discriminative validity was evaluated by examining the effect of DT conditions (single task versus dual-task) on; a) spatiotemporal gait measures (average and coefficient of variation) and b) visuomotor and visuospatial executive performance measures. Twenty-five community-dwelling individuals median age 65 (range 61-67) were recruited from a Fitness Facility. Participants performed a computerized visuomotor tracking task and a visuospatial executive game task in standing and while treadmill walking. Testing was conducted on two occasions, one week apart. Moderate to high test-retest reliability (ICC values of 0.65 to 0.88) were observed for spatiotemporal gait variables No significant mean difference occurred between test periods in any gait variable. Moderate test-retest reliability (ICC values of 0.6 to 0.65) was observed for measures of visuomotor and visuospatial executive performance during treadmill walking. Significant DT effects were observed for both spatiotemporal gait variables and visuospatial executive performance measures. This study demonstrates the reliability and reproducibility of the computer-based assessment tool for dual task treadmill walking. The high to moderate ICC values and the lack of systematic errors in the measures indicate that this tool has the ability to repeatedly record reliable data from community-dwelling older adults. The present computerized dual-task protocols broaden the types of standardized visuomotor and visuospatial executive activities for use with DT treadmill walking that has previously been reported.